Menggugah Pandangan Sempit Tentang Manusia dengan Memahami Hakikat Manusia dalam Perspektif Metafisika - Sakunab, Marius Deparno; Riyanto, F.X Armada (Fakultas Ilmu Budaya, Universitas Jambi, 2023)
This paper focuses on understanding human nature from a metaphysical perspective. This paper is done because of the author's unrest over the humanitarian crisis experienced by the world, one of which is caused by the narrow views of certain parties which results in the mistreatment of others. The purpose of writing is to realize these narrow views that humans need to be respected and valued instead of being destroyed. The problem is that humans often experience mistreatment from the cruel actions of certain parties because of a narrow view of humanity that does not understand the nature of humans as God's creation. This research uses two methods, namely the case study method and the literature study method. The results of the research show that it turns out that in the metaphysical view, humans are understood as subjects (existing) on their own who must be treated well, respected, and appreciated. Human nature as a subject should be seen from its fullness and totality because humans as